Randomised, Double Blind, Multicentre, Placebo Controlled Study of Sulodexide in the Treatment of Venous Leg Ulcers - Coccheri, Sergio; Scondotto, Gaetano; Agnelli, Giancarlo; Aloisi, Daniele; Palazzini, Ernesto; Zamboni, Villiam; for the venous arm of the SUAVIS (Sulodexide Arterial Venous Italian Study) Group (Thrombosis and Haemostasis, 2002)
Sulodexide, a highly purified glycosaminoglycan, was investigated for treatment of venous leg ulcers. Patients (n = 235) undergoing local treatment including wound care and compression bandaging, were randomised to receive either sulodexide or matching placebo for three months. Primary study endpoint was complete ulcer healing after 2 months; secondary endpoints were ulcer healing at 3 months and the time-course changes of ulcer areas.The proportion of patients with complete ulcer healing was higher with sulodexide at 2 months (p = 0.018) and 3 months. The “number needed to treat” to obtain one additional patient healed with sulodexide was 7 at 2 months and 5 at 3 months. The changes in ulcer surface area with time were significant for sulodexide only (p = 0.004). Fibrinogen significantly decreased in sulodexide patients (p = 0.006).In conclusion, sulodexide associated with local treatment proved to be effective and well tolerated in the management of venous leg ulcers.
Keywords: Sulodexide; chronic venous insufficiency; venous leg ulcer; glycosaminoglycans